Factors Affecting Owners' Choice of Nutritional Supplements in Dressage and Eventing Horses. (June 2014) - Gemmill, R; Agar, C; Freeman, S; Hollands, T
Abstract : Introduction: Horse owners are faced with a vast range of supplements and different sources of information. The aim of this study was to evaluate sources of information used by owners/riders when choosing supplements for competition horses, their opinions on different sources of information and evaluation of factors that affect their decisions. Methods: A mixed methods (open and closed questions) online questionnaire was distributed through British Eventing and Dressage websites to owners/riders of dressage and/or event horses, to collect data on the demographics of the owner/rider and their horses, sources of information used when choosing nutritional supplements, and their opinion on these different sources. Data was evaluated using descriptive analysis and Chi‐squared tests for quantitative data, and thematic analysis for qualitative data. Results: 757 responses met the inclusion criteria, and owners/riders competed at dressage and eventing from unaffiliated novice to affiliated advanced level. Veterinary surgeons were considered the most reliable source of information, followed by nutritionists, research studies, coach/trainer and other horse owners. 'Other horse owners' were the top source (18% of participants) for the participants' most recent choice of supplement. Respondents with a higher education qualification were significantly more likely to use research papers as a source of information (P<0.005). Owners/riders under 34 years of age were significantly more likely to use a coach / trainer as a source of information (P<0.005). Conclusions: Horse owners identified veterinary surgeons, nutritionists and research papers as reliable sources of information, but ultimately most chose their supplement based on recommendations of other owners or coaches/trainers. Ethical Animal Research: The study was reviewed and approved by the School of Veterinary Medicine and Science Ethics Committee at the University of Nottingham.Sources of funding: School of Veterinary Medicine and Science at the University of Nottingham.Competing interests: Teresa Hollands is employed by Dodson and Horrell Ltd.